(The Contribution of Agroforestry to the Income of Farmers in Forest Village Community Institution (LMDH) Tulungrejo Village Subdistrict Bumi Aji Batu City) - Ningsih, Ratih Hesti; Triwanto, Joko; Chanan, Mochamad (Universitas Muhammadiyah Malang, 2020)
ABSTRACTThe transformation of forest land into agricultural land that occurs and develops over time, in line with the increasing area of forest converted into other business land causes many problems. Agroforestry is expected to be a solution to overcome the problems arising from land conversion as well be the solution to the problem of food and economic society community. The purpose of this study is to determine and assess the management of agroforestry and calculate the contribution of agroforestry to to revenues pesanggem in the Forest Village Community Institution (LMDH) Tulungrejo Village Subdistrict Bumi Aji Batu City. The method used to approach the qualitative (descriptive) and quantitative while to analyze the data in this study are multivariate methods Structural Equation Model (SEM) using IBM SPSS AMOS program 23. The subject of this research is population in this study are members LMDH Tulungrejo Village Subdistrict Bumi Aji. The results showed that the Management Agroforestry positive and significant impact on revenue pesanggem, the better management of agroforestry pesanggem the higher income, and vice versa. In addition, the results of analyzing the correlation (r) 0.741 and 0.000 sig> 0.05 indicate that there is a correlation between land and total income. While the relationship between the two variables are highly correlated and strong is 74.1%. Direction of the relationship is positive for positive r, meaning the area of a farmland it will increase the amount of revenue obtained. The direction of the relationship is positive because r is positive, meaning that the wider the area of land will increase the amount of income earned. While the results of the calculation of the influence of agroforestry management and the contribution of agroforesty to pesanggem income amounted to 71.8%, while the remaining 28.2% of the variant of pesanggem income was influenced by other factors outside of agroforestry management and the contribution of agroforestry. Keywords: Agroforestry, Income, LMDH and Bumi Aji